Analisis Akuntansi Pertanggungjawaban Sebagai Alat Pengendalian Biaya Produksi Pada Pt. Perkebunan Nusantara Iv Regional Ii Unit Kebun Bah Birong Ulu - Surya Sanjaya; M Irsan; Jamilah Agustina (Jurnal Riset Akuntansi dan Bisnis, 2026)
This study employs a descriptive method with a qualitative approach. Data collection was conducted through interviews and document analysis, utilizing data on production cost budgets and actual expenditures for the 2020–2024 period. The results indicate that the company has implemented responsibility accounting, evidenced by a clear organizational structure, the preparation of production cost budgets, cost classification, cost recording systems, and periodic responsibility reports. However, there remain unutilized production cost budget allocations, with the percentage of unspent funds tending to increase annually. This suggests that budget preparation does not yet fully reflect actual operational conditions, thereby preventing the control function from operating optimally. Overall, responsibility accounting has played a role in supporting production cost control through the processes of planning, execution, and evaluation; however, improvements are still needed, particularly regarding the preparation of more accurate and realistic budgets.